A Review on: Advances in colon targeted drug delivery system for oral site specific Therapeutics - Switi S. Naktode; Dr. Shrikant P. Pande; Shrushti P. Wagh; Shrirang A. Virkhare; Sidhhi P. Kalbande (Asian Journal of Pharmaceutical Research and Development, 2026)
The delivery of the drug into the eye has always been a big problem because of the organs and physiological peculiarities of the eye: the eye is blinking, tears are flowing, and nasolacrimal drainage. The traditional dosage delivery methods such as eye drops and eye ointments are usually associated with poor bioavailability and poor therapeutic potential. In order to address these constraints, in situ gels in the eye have become one of the promising ones to provide long residence time, greater compliance, and regulated drug delivery in patients. These formulations are embedded as low-viscosity solutions undergoing a sol-to-gel transition to environmental stimuli, e.g. pH, temperature, or ionic strength in the ocular cavity. Some of the polymers that are used as either natural or synthetic polymers such as chitosan, carbopol, poloxamer, and gellan gum are very important in giving the gelling property and biocompatibility. The design of ophthalmic in situ gels entails rather sensitive areas such as viscosity, clarity, drug entrapment capacity, gelation capacity, and sterility that have direct influence on therapeutic performance. Rheology, gel strength, in vitro release studies, and ocular irritation tests are the methods of characterization that are important to evaluate the quality of the formulations. This review outlines the latest progress in the design of strategies to be used in the formulation of ophthalmic in situ gel, the criteria of evaluation, and the therapeutic use and outlines how it can be used as an efficient substitute to the traditional methods of ocular delivery systems.